Avaliando a dívida técnica em produtos de código aberto por meio de estudos experimentais - Vieira, Igor Rodrigues (2014)
The metaphor of technical debt (TD) is very useful for Software Engineering, it is directly related to the context of evolution and maintenance in the life cycle of a product. It can be understood as a relation between costs and effects, of short and long term, associated with project decisions during the software development process. Currently, large companies and some government sectors still have restrictions in adopting open source products by uncertainties related to its quality and reliability. In this context, this study aims to evaluate the technical debt in open source products in order to demonstrate the feasibility of this approach to evaluate the software quality. For this, were performed experimental studies, contemplating the automated data collection for a significant set of products open source, having as input its source code. These products were evaluated by SonarQube Platform, which enables collect several metrics about the quality of the source code - including the technical debt. The interpretation of the collected data allowed the analysis of the TD evolution for these products, the classification of the projects and the verification of the representativeness of the quality axis that make up the TD. The results suggest that most of the projects evaluated have shown decreased TD along their versions and they showed slightly elevated values of the metric. Another contribution is that the quality axis Coverage, Violations and Complexity is presented as the main contributors to the TD’s increase of from the set of product evaluated. It was also possible to verify the existence of a correlation between the TD implementation and the SQALE methodology, with regard assessing software quality evaluating.